2018
DOI: 10.1016/j.kint.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6/Stat3 signaling has an essential role in the host antimicrobial response to urinary tract infection

Abstract: The signaling networks regulating antimicrobial activity during urinary tract infection (UTI) are incompletely understood. Interleukin-6 (IL-6) levels increase with UTI severity, but the specific contributions of IL-6 to host immunity against bacterial uropathogens are unknown. To clarify this we tested whether IL-6 activates the Stat3 transcription factor, to drive a program of antimicrobial peptide gene expression in infected urothelium during UTI. Transurethral inoculation of uropathogenic Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 57 publications
2
48
0
4
Order By: Relevance
“…Knowing that IFN-γ can regulate IL-13 responses 30 , these observations indicated that following viral vector-based vaccination, at the cDC level the differential environmental immune responses to IL-13 are not only determined/regulated by STAT3/STAT6, but also by TGF-β1 and IFN-γ either collaboratively or independently, which was consistent with cancer/inflammation studies [53][54][55][56] . Interestingly, rapid STAT3 activation has shown to control some viral infections 51,57,58 whilst, STAT6 independent mechanisms have also been associated with effective antibody differentiation 28 . Moreover, IL-13 mediated enhanced IFN-γ signalling has been shown to exacerbate respiratory viral infections 31,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that IFN-γ can regulate IL-13 responses 30 , these observations indicated that following viral vector-based vaccination, at the cDC level the differential environmental immune responses to IL-13 are not only determined/regulated by STAT3/STAT6, but also by TGF-β1 and IFN-γ either collaboratively or independently, which was consistent with cancer/inflammation studies [53][54][55][56] . Interestingly, rapid STAT3 activation has shown to control some viral infections 51,57,58 whilst, STAT6 independent mechanisms have also been associated with effective antibody differentiation 28 . Moreover, IL-13 mediated enhanced IFN-γ signalling has been shown to exacerbate respiratory viral infections 31,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen recognition by urothelial cells has been suggested to stimulate IL-6 secretion 43 with key roles in limiting urothelial invasion and ascending infection. 44 Analysis by SPRING revealed strong upregulation of this molecule within the infected urothelium and topical inhibition by local intraurethral administration of antibodies against IL-6 aggravated the infection. Interestingly, the expression of IL-6 strongly correlates with bacterial burden in humans 45,46 and local production of IL-6 by urothelial cells was recently suggested.…”
Section: Discussionmentioning
confidence: 98%
“…The MICs of 2Abz 23 S 29 and ciprofloxacin (cip) were determined by broth microdilution assay, according to a previously reported protocol. 17 In general, bacteria were grown overnight in LB for 24 h and were diluted to approximately 5 × 10 5 colony-forming units (CFU/mL) in Mueller Hinton Broth (MHB, Difco, Becton Dickinson Co., Sparks, MD, USA).…”
Section: Minimum Inhibitory Concentration (Mic) Assaymentioning
confidence: 99%
“…Interactions between ciprofloxacin (cip) and 2Abz 23 S 29 were studied by a broth microdilution checkerboard titration assay. Serial dilutions of ciprofloxacin were tested in the presence of serial dilutions of 2Abz 23 S 29 .…”
Section: Checkerboard Titration Assaymentioning
confidence: 99%
See 1 more Smart Citation